Study of diversity in thermo-tolerant advanced lines of Wheat (Triticum aestivum L.) for Morpho-physiological, Yield and its Contributing Traits - Aggarwal, Rajesh; Marker, Shailesh; Phansal, Ankit (Journal of Cereal Research, 2021)
The present study was carried out to examine the genetic diversity among 151 thermo-tolerant advanced breeding lines of wheat for two experimental years during Rabi 2017-18 and Rabi 2018-19 in randomized block design in an area of 312 m2 at Field Experimentation Center, Department of Genetics and Plant Breeding, SHUATS, Allahabad. The data were recorded in both the seasons for total 23 traits i.e. 18 quantitative characters to study variability, heritability, genetic advance and genetic divergence and 5 morphological characters. ANOVA showed significant differences for all the characters except flag leaf width, in both experimental seasons and for gluten content in season Rabi 2018-19 indicating the presence of a substantial amount of genetic variability which thus revealed different genetic backgrounds of genotypes. High estimates of both GCV and PCV were observed for biological yield in both experimental years. High heritability with high genetic advance was recorded for all quantitative characters except flag leaf width and gluten content indicating the predominance of additive gene effects and hence the possibilities of effective selection for the improvement of these traits. D2 analysis grouped these lines into 10 clusters in which cluster VII was biggest cluster with 26 lines. Further diversity analysis revealed that cluster IV and VII followed by Cluster VI and Cluster VII were most divergent from each other, and the genotypes present in them may be used as parents for further hybridization program to develop desirable heat type in wheat. Analysis of 5 Morphological characters i.e. leaf type, rachis colour, leaf shape, waxiness and stay green habit, depicted that HUW-213 x NW-1076 followed by HALNA x RAJ-4037 were found above average yielders and terminal heat tolerant primarily due to their semi-erect leaf type, green rachis color, broad leaf shape, stay green habit and less days to maturity as compared to checks.